The Effect of Price on Purchasing Decisions for Starbucks in the Mega Mas Manado Area - Gerungan, Elke Keezia; Tumbel, Tinneke M; Aseloei, Sandra (Productivity, 2024)
This study uses quantitative methods with simple linear regression analysis techniques. The sample used was 50 samples. Validity test, reliability test, normality test, simple correlation coefficient test, partial test, and determination test were used. The result is that price has a positive and significant effect on purchasing decisions at Starbucks Megamas Manado Area with a large influence of 63.2%.